A Study on the Level of Awareness and Perception of Investors Regarding Socially Responsible Investing in Sikkim - Ritesh Chhetri; Deepa Sharma (East Asian Journal of Multidisciplinary Research, 2022)
SRI also refers to ethical investing and explains the combination of Environment, Social and Governance (ESG) aspects into the process of investment process. The concept of socially responsible investment which originated mostly from North American and European countries is now spread to other developed and developing countries. There has been increasing awareness with respect to SRI in the context of developed countries as evidenced by different social responsibility indices that have been framed like FTSE KLD 400 index. These indices also include companies from developing and emerging countries. In Indian context there are indices like NIFTY 100 ESG index, NIFTY 100 enhanced ESG index which is based on the ESG score of the company and has base year of April 2011. In this regard this study aims to study the awareness and perception level of investors in the context of a small state of Sikkim regarding Socially responsible Investment.